Nutritional intake according to injury extent in ulcerative colitis patients - Urbano, A. P S [UNESP]; Sassaki, Ligia Yukie [UNESP]; Dorna, M. S. [UNESP]; de Barros Leite Carvalhaes, M. A. [UNESP]; Martini, L. A.; Ferreira, Ana Lúcia dos Anjos [UNESP] (Wiley, 2013)
Background: Ulcerative colitis (UC) is often associated with nutritional deficiency, which appears to contribute to the progression of UC severity. The present study aimed to evaluate nutritional status and dietary intake in UC remission patients. Methods: The present study comprised a cross-sectional study in which variables such as extent of disease (distal colitis, left-sided colitis, pancolitis), remission period, sex and age were recorded. Extent of disease was assessed by the results of a colonoscopy and dietary intake was evaluated by using 3-day, 24-h recalls. A Kruskall-Wallis test was used to compare the intake of macro- and micronutrients among the three study groups. The analysis was complemented by the Mann-Whitney test. A logistic regression analysis was performed to identify predictive factors of extent of disease (pancolitis versus left-sided colitis versus distal colitis). Results: The median (range) age of the 59 patients was 49.0 (37.0-63.0) years and 53.3% were female. Twenty-six (44.1%) patients had distal colitis, 11 (18.6%) patients had left-sided colitis and 22 (37.3%) patients had pancolitis. A high probability of an inadequate intake of fibre (100%), fat soluble vitamins (>40% for vitamin A and >95% for vitamin E), vitamin C (>34%), calcium (>90%) and magnesium (>50%) was identified in the study group. Vitamin D intake (odds ratio = 0.60; 95% confidence interval = 0.39-0.94; P < 0.05) was significantly associated with increased intestinal damage. Conclusions: A large number of individuals showed an inadequate intake of nutrients. In addition, the consumption of vitamin D was significantly associated with extent of disease. © 2013 The British Dietetic Association Ltd.
Keywords: Inadequate intake; Nutrient intake; Nutritional assessment; Overweight; Ulcerative colitis; Vitamin D